Dimensional Deviations Determine Canned Packaging Rejection Rates Using Failure Mode Analysis: Deviasi Dimensi Menentukan Tingkat Penolakan Kemasan Kaleng Menggunakan Analisis Mode Kegagalan - Bima Aulia Cahya; Atikha Sidhi Cahyana (Proceedings of The ICECRS, 2024)
General Background The packaging industry requires rigorous quality control systems to satisfy stringent medical and consumer standards. Specific Background PT United Can recently reported a 2.16% rejection rate in rigid container production, exceeding the allowable tolerance limit. Knowledge Gap While general product evaluations exist, precise prioritization of specific operational errors in medical-grade aluminum and steel receptacles remains necessary to minimize production waste. Aims This study evaluates operational errors to isolate the highest defect contributors and formulate targeted corrective procedures. Results Pareto calculations and risk evaluations reveal that structural non-conformities constitute 54% of total rejections, earning the highest Risk Priority Number of 245. This critical error originates from imperfect machine rounding, preventing proper closure assembly, while rust and dents present significantly lower risks with scores of 90 and 30, respectively. Novelty This research isolates imperfect rounding mechanisms as the primary quantitative risk factor in rigid container manufacturing, providing a direct metric for targeted intervention. Implications Manufacturers must prioritize strict visual monitoring and precise machine calibration to minimize closure assembly errors and maintain industry competitiveness. Highlights: Imperfect machine rounding produces closure assembly errors and represents the highest operational risk. Visual monitoring protocols mitigate manufacturing errors and ensure consistent product standards. Rust and dents constitute minor production risks compared to structural inconsistencies. Keywords: Quality Control, Risk Priority Number, Rigid Containers, Defect Mitigation,Machine Calibration